Phytochemical Screening and Larvicidal Evaluation of Phyto-synthesized Silver Nanoparticles using Palmyra Palm Sprout Extract - Wilson Lamayi Danbature; Zaccheus Shehu; Muhammad Mustapha Adam; Ahmed Mohammed Bello (Biogenesis: Jurnal Ilmiah Biologi, 2020)
One of the objectives of nanotechnology is to synthesize effective nanoinsecticides in a bid to reduce the prevalence of the numerous diseases caused by mosquitoes. This synthesis is even more vital in cases where phytochemicals from plant extracts are used as reducing agents. This study aims to determine the phytochemicals present in Palmyra (Borassus aethiopum) sprout extract, perform green synthesis of silver NPs with the sprout extract, and spectroscopic investigation using FT-IR and UV-Visible spectrophotometers, in addition to the main aim of evaluating the AgNPs’ applications as a nano-larvicide. For this study, a total of ten phytochemical analyses was performed. Subsequently, the sprout extract was used as a reducing agent in the synthesis of silver nanoparticles (AgNPs). Characterization with Fourier transform infrared and Ultraviolet-visible spectrometry was then carried out to confirm the synthesis. In addition, the AgNPs were further analyzed for larvicidal potency against 1st, 2nd, 3rd and 4th instars Culex quinquefasciatus mosquito larvae, at interval concentrations of 5, 10, 20, 25, and 50 ppm. The results confirmed the presence of alkaloids, flavonoids, saponins, coumarins, glycosides, tannins, phenols as well as quinines, however, sterols, steroids, and terpenoids were not detected. The LC50 and LC90 values discovered to be 9.103 ppm and 134.463 ppm with a correlation of 0.815, as well as 10.316 ppm and 118.810 ppm with a correlation of 0.801, for the 1st and 2nd instars, respectively. Meanwhile, the 3rd and 4th instars had LC50 and LC90 values of 17.585 ppm and 179.052 ppm, respectively, with a correlation of 0.807. This study provides a basis for extracting and analyzing the reduction potential of the phytochemicals present in the sprout extract, as well as the application of AgNPs, in controlling the mosquito larvae population.